POLA INFLASI DAN PENGANGGURAN DI NEGARA NEGARA ASEAN TAHUN 2003 â€“ 2012 - Reiny Seruni (Jurnal Ekonomi Pembangunan, 2014)
This Research aims to analyze the relation between Inflation and Unemployment in ASEAN countries from 2003 until 2012. The variable used are Inflation and Unemployment. Inflation measured from the development of consumer price index and unemployment in terms of open unemployment. This research uses qualitative and quantitative analysis techniques, the quantitative analysis used are panel data regression. The result showed that in statistical variableÂ Inflation and Unemployment in ASEAN countries in 2003-2012 significant and has negative relations. Keywords: Inflation, Unemployment, Phillips Curve